HUBUNGAN TINGKAT KECERDASAN EMOSIONAL DENGAN MEKANISME KOPING PADA REMAJA SEKOLAH MENENGAH ATAS - Navyanto, Krisna Dwi; Zunaedi, Rosly; Ekasari, Rizqiana Dita (STIKES Widyagama Husada, 2025)
The use of maladaptive coping mechanisms frequently becomes the reason behind adolescents failure to resolve a problem or manage their sources of stress effectively. This can lead to mental health disorders among adolescents. The use of coping mechanisms in adolescents can be influenced by various factors, one of which is their level of emotional intelligence. The aims of this study was to analyze the correlation between the level of emotional intelligence and coping mechanisms among high school students at SMA Negeri 1 Singosari. This study employed a quantitative observational research method with a cross-sectional approach involving 110 twelfth-grade high school students as respondents. Data were collected in November 2024 using total sampling. The instruments used were The Schutte Self-Report Emotional Intelligence Test (SSEIT) and Coping Orientation to Problems Experienced Inventory (Brief COPE) questionnaires. The analysis was conducted using the Gamma test. A total of 93 respondents (84.5%) exhibited a moderate level of emotional intelligence, dominated by the aspect of managing emotions. Additionally, 104 respondents (94.5%) demonstrated adaptive coping mechanisms, with most using problem-focused coping strategies. There is significant correlation between the level of emotional intelligence and coping mechanisms (p = -0.943).